The Effect of Learn English Vocabulary Application on Senior High School Students' Vocabulary Mastery - Salsabila, Meida Adenia; Wijaputra, Bambang Arya; Fitriyah, Siti Masrifatul (English Education Study Program, 2022)
This study was conducted to investigate the effect of Learn English Vocabulary application on Senior High School students’ vocabulary mastery. Based on the preliminary study, it was known that the tenth grade students had difficulty in learning English language because of the unfamiliar words in the material. This study applied quantitave method and using quasi-experimental design. The two classes were chosen as participants for this research, one class as the experimental group and the other class as the control group. The experimental group was taught vocabulary by using the Learn English Vocabulary application, meanwhile the control class was taught conventionally by pictures and worksheets. The finding of this study showed that the experimental group got higher mean score (93.06) than the control group (77.65). Therefore, it could be concluded that Learn English Vocabulary application had a significant effect on senior high school students’ vocabulary mastery. Key Words: English vocabulary; mobile assisted vocabulary learning; mobile application